REMARKS ON THE TRANSFORMATION OF THE POLISH BANKING SYSTEM BY THE REFORMS AFTER 1989 - Rafał, Sura (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
Summary This work concentrates on the main direction of changes in the field of the Polish Banking Law after 1989. All the changes observed at that time were directly or indirectly related to the adjustment of the Polish legislation to the regulation of the European Union. They concerned the following areas: building a new legal system regulating bank operations; transforming the National Bank of Poland into a modern central bank which does not run a commercial activity; establishing private commercial banks, including foreign capital banks; privatizing commercial banks. Keywords : Polish Banking Law, European Union, National Bank of Poland, commercial banks.